Marine mammal records from Iran - Braulik , Gillian T.; Ranjbar , Sharif; Owfi , Fereidoon; Aminrad , Teymour; Mohammad , Seyed; Dakhteh , Hashem (J. Cetacean Res. Manage., 2023)
Iran has 1,700km of coastline that borders the Persian Gulf and the Arabian Sea in the northwest Indian Ocean. Apart from a handful of records, almost nothing is known about which marine mammal species occur in Iranian waters. This review was conducted to fill this information gap. A total of 127 marine mammal records of 14 species were compiled from Iranian coastal waters. Ninety-nine were from the Persian Gulf, 26 from the Gulf of Oman and 2 were of unknown location. Records of finless porpoise (Neophocaena phocaenoides) (25), Indo-Pacific humpback dolphin (Sousa chinensis) (24) and Indo-Pacific bottlenose dolphin (Tursiops aduncus) (22) were by far the most numerous, a probable reflection of their inshore distribution and local abundance. Other species recorded were long-beaked common dolphin (Delphinus capensis tropicalis), roughtoothed dolphin (Steno bredanensis), striped dolphin (Stenella coeruleoalba), spinner dolphin (Stenella longirostris), Risso’s dolphin (Grampus griseus), false killer whale (Pseudorca crassidens), sperm whale (Physeter macrocephalus) and dugong (Dugong dugon). Records of 26 mysticetes were compiled, 10 of which were tentatively identified as Bryde’s whales (Balaenoptera edeni), 1 possible fin whale (Balaenoptera physalus), 3 humpback whales (Megaptera novaeangliae) and the remainder were not identified to species. The largest threat to small cetaceans in Iran is likely to be incidental capture in fishing gear. Nine finless porpoises were recorded as bycatch and this and other coastal species may be declining due to unsustainable mortality rates. Some of the world’s busiest shipping lanes pass through Iranian waters and ship strikes are likely to be the largest threat to mysticetes in the area.